An Analysis of Code Mixing That is Used by The Models and The Judges in Indonesia’s Next Top Model Cycle 3 - Raflis, Raflis; Pribahty Waruwu, Welly Pribahty (Fakultas Sastra Universitas Ekasakti, 2024)
This research discusses the types and functions of code mixing found in the